1993
DOI: 10.1002/pola.1993.080310311
|View full text |Cite
|
Sign up to set email alerts
|

Linear all‐ortho oligomers of phenol–formaldehyde resins. I. Preparations, characterizations, and solution properties

Abstract: Three kinds of all‐ortho methylene‐linked phenolic oligomers, i.e., 4‐tert‐butylphenol (BP), phenol (AO), and O‐methylated BP (BPM), were prepared with good yields and their dilute solution properties were studied. In acetone, all of these oligomers are highly solvated and molecularly dispersed. In chloroform, however, AO and BP molecules strongly form hydrogen bonds among themselves. By intramolecular and intermolecular hydrogen‐bondings, a large portion of the dimers and the trimers of AO and BP associate to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…(OPLS_2001 forcefield, MCMM, 1,000 steps). 37 . The phenolic trimer 3 (5.50 g, 11.6 mmol) was dissolved in THF (130 ml) and DMF (10 ml).…”
Section: Resultsmentioning
confidence: 99%
“…(OPLS_2001 forcefield, MCMM, 1,000 steps). 37 . The phenolic trimer 3 (5.50 g, 11.6 mmol) was dissolved in THF (130 ml) and DMF (10 ml).…”
Section: Resultsmentioning
confidence: 99%
“…Many workers have since investigated this phenomenon in higher oligomers 25,27,30 . Higher acidity values are observed with increasing chain length as found for linear oligomers with a terminal p-nitrophenol unit, which may stabilize the mono-anion.…”
Section: Statistical Novolac Resinsmentioning
confidence: 99%
“…Investigations of the reactivity of ortho-linked oligomers towards formaldehyde under acidic conditions showed that as the chain length is increased, the shielding and deactivating effects of intramolecular hydrogen bonding decreased the reactivity 34 . There is recent evidence 25,35,36 to suggest that in solution at least, a large proportion of the ortho-linked oligomers adopt pseudo-cyclic conformations. The molecular freedom of liquid resins may be somewhat restricted by such hydrogen bonding, thereby hindering their ability to adopt conformations favourable for chain extension or crosslinking 31 .…”
Section: Structurally Uniform 'Pure' Novolac Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamagishi et al [11] reported the synthesis of methylene-linked para-tertiary-butylphenol oligomers through tri-nuclear precursor with hydrochloric acid as the catalyst. The limitation of this type is that the viscosity of the system is too high to stir in the late stage of polymerization, which is detrimental for the preparation of resins with high molecular weight.…”
Section: Introductionmentioning
confidence: 99%